La lettura bilingue della poesia autotradotta: Un caso di edizione bilingue (TEST Ticontre. Theory Text Translation, 2024)
This article starts from the hypothesis that the bilingual reading of self-translated poetry presents a new key of interpretation, different from both the monolingual and the bilingual reading of translation. The study is an investigation of this key, as it appears in the reading of the poetry of Gentiana Minga (b. 1971), an author of Albanian origin, active in Italy since the 90s. Through the reading of her latest collection of poems, a bilingual edition written in Italian and partly self-translated into Albanian, published by Terra d’ulivi edizioni in 2021, this study aims to demonstrate that the self-translated version in a bilingual edition is not read as a translation, but as part of one whole multilingual text. Quest’articolo parte dall’ipotesi che la lettura bilingue della poesia autotradotta offra una nuova chiave di lettura, diversa sia dalla lettura monolingue, sia da quella bilingue della traduzione. Lo studio è un’indagine di questa chiave, così come appare nella lettura della poesia di Gentiana Minga (n. 1971), autrice di origine albanese attiva in Italia dagli anni ’90. Attraverso la lettura della sua ultima raccolta di poesie, un’edizione bilingue scritta in italiano e in parte autotradotta in albanese, pubblicata da Terra d’ulivi edizioni nel 2021, questo studio si propone di dimostrare che la versione autotradotta in un’edizione bilingue non viene letta come traduzione, ma come parte di un unico testo multilingue.